Parâmetros físicos dos atuns capturados em cardumes associados pela frota de pequena escala no atlântico oeste equatorial - Rebouças, Lucas de Oliveira Soares (Universidade Federal Rural do Semi-Árido, 2020)
The tuna and related group is an important global fishing resource, usually tuna fishing is characterized by the predominance of the industrial segment, being carried out by large vessels, with high technological level, for the capture, storage and processing on board. In the Northeast with the exhaustion of stocks traditionally exploited, a large part of the artisanal fishing fleet is being adapted in search of alternative fisheries, such as tuna. The great problem of artisanal fishing is found in the low quality of the fish, due to the low access to technology and the absence of measures of good handling practices on board by the fishermen. The objective of this work is to evaluate the quality of tuna caught in artisanal fleets in the equatorial western Atlantic, identifying which factors on board are important for determining the quality of fish. For this, six (06) shipments were carried out during a year in the artisanal fleet of the municipality of Areia Branca - RN. The variables still analyzed on board were furcal length, species, initial temperature, initial pH, ice days, deck time and slaughter method. Upon disembarking, the fish were taken to the Sensory and Instrumental Analysis Laboratory at UFERSA for further analysis. The quality variables analyzed were pH, luminosity (L *), red content (a *), yellow content (b *), water retention capacity (%), post-cooking weight loss and shear strength . Principal component analysis (PCA) was used to verify which variables are important for determining the quality of tuna. The relationship between the variables were analyzed using simple regression analyzes, with Pearson's correlation, in order to verify if there was a correlation (negative / positive) between the variables. The first two main components of the ACP accounted for almost 70% of the variance. Where, the furcal length, ice days and deck time were the main variables on board responsible for determining the final quality of the tuna
Keywords: Pesca artesanal; Scombridae; Qualidade do pescado; Artisanal fishing; Scombridae; Seafood quality; CIENCIAS AGRARIAS::MEDICINA VETERINARIA